Wave spectral response to sudden changes in wind direction in finite-depth waters. (July 2016) - Aijaz, Saima; Rogers, W. Erick; Babanin, Alexander V.
Highlights: High resolution wave modelling at microscales of 30 s and less than 10 m. Use of XNL (exact) and DIA (approximate) models for nonlinear energy transfer. Directional response of model 5 min behind observations and 10 min after wind turn. Testing of new wind input, whitecapping, swell dissipation, bottom friction terms. Improved model skill using new source terms. Abstract: The response of a wind-sea spectrum to sudden changes in wind directions of 180° and 90° is investigated. Numerical simulations using the third-generation wave spectral model SWAN have been undertaken at micro timescales of 30 s and fine spatial resolution of less than 10 m. The results have been validated against the wave data collected during the field campaign at Lake George, Australia. The newly implemented 'ST6' physics in the SWAN model has been evaluated using a selection of bottom-friction terms and the two available functions for the nonlinear energy transfer: (1) exact solution of the nonlinear term (XNL), and (2) discrete interactions approximation (DIA) that parameterizes the nonlinear term. Good agreement of the modelled data is demonstrated directly with the field data and through the known experimental growth curves obtained from the extensive Lake George data set. The modelling results show that of the various combinations of models tested, the ST6/XNL model provides the most reliable computations of integral and spectral wave parameters. When the winds and waves are opposing (180° wind turn), the XNL is nearly twice as fast in the aligning the young wind-sea with the new wind direction than the DIA. In this case, the young wind-sea gradually decouples from the old waves and forms a new secondary peak. Unlike the 180° wind turn, there is no decoupling in the 90° wind turn and the entire spectrum rotates smoothly in the new direction. In both cases, the young wind-sea starts developing in the new wind direction within 10 min of the wind turn for the ST6 while the directional response of the default physics lags behind with a response time that is nearly double of ST6. The modelling results highlight the differences in source term balance among the different models in SWAN. During high wind speeds, the default settings provide a larger contribution from the bottom-friction dissipation than the whitecapping. In contrast, the whitecapping dissipation is dominant in ST6 while the bottom-friction generated by the new model with ripple formation provides a significant contribution during strong winds only. During low wind speeds and non-breaking wave conditions, a separate swell or nonbreaking dissipation source term continues the decay of waves that cannot be dissipated by the whitecapping dissipation function.